Penerapan Model Pembelajaran Kooperatif Tipe Student Team Achievement Divisions (STAD) untuk Meningkatkan Hasil Belajar Matematika Siswa Kelas V SD Negeri 24 Toboali - Marwiyah Marwiyah; Didi Kriswanto (TIRAI: Jurnal Program Studi Manajemen Pendidikan Islam, 2023)
This study aims to improve mathematics learning outcomes through the application of a cooperative learning model of the Student Teams Achievement Divisions (STAD) type in V grade students at SD Negeri 24 Toboali. This research is a type of classroom action research. The subjects in this study were all V grade students at SD Negeri 24 Toboali, totaling 24 students consisting of 13 boys and 11 girls. The object of this research is the results of learning mathematics in fifth grade students of SD Negeri 24 Toboali. Data collection techniques using observation, written tests, and documentation. This research was said to be successful if 80% of students achieved the KKM, namely 68. The results showed that the Application of the STAD Type Cooperative Learning Model was proven to be able to improve Mathematics Learning Outcomes for Class V SD Negeri 24 Toboali in the Academic Year 2022/2023. This is evidenced by the completeness of student learning outcomes in cycle I and cycle II which experienced a significant increase. The average score of students who completed the first cycle was 62.08 with a completeness percentage of 58.33% and in the second cycle the average student score increased to 75.41 with a completeness percentage of 83.33%. In addition, it was also followed by a positive increase in changes in self-confidence, discipline, and responsibility